Strategy Analysis Of The National Zakat Community (BAZNAS) Of Tanah Datar Regency In Increasing Non-Asn Zakat Collection - Yokal Afriko; Asrida; Gampito; Widi Nopiardo (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
BAZNAS of Tanah Datar Regency has successfully optimized zakat collection through an automated salary deduction system for Civil Servants (ASN). However, a significant challenge persists in the non- ASN sector, where contributions remain remarkably low, accounting for only 1.94% in 2023 and decreasing to 1.77% in 2024. Despite this, the potential zakat from agriculture, trade, and professional sectors is highly significant if managed professionally. This qualitative field research aims to analyze strategies for increasing non-ASN zakat collection, alongside its supporting and inhibiting factors. The results indicate that the strategy is executed through three stages. First, strategy formulation involves mapping potential muzakki and analyzing internal-external conditions. Second, implementation includes establishing fundraising volunteers, optimizing the role of empowerment preachers (da’i), providing zakat pick-up services, and conducting extensive socialization via direct and digital media. Third, periodic evaluations are conducted to ensure program sustainability. Supporting factors include an increasing number of local volunteers and policy support from the Regional Government and the Ministry of Religious Affairs. Conversely, the primary inhibiting factors are low zakat literacy, limited understanding among some religious leaders regarding organizational zakat management, and a strong traditional culture of distributing zakat directly to mustahik without involving official institutions.